2021
DOI: 10.31234/osf.io/hv4cb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Disentangling dynamic affect trajectories for distinct depression courses during the COVID-19 pandemic

Abstract: Background. Why does adversity lead to mental health complaints in some, but not others? Individual differences in the development of depressive complaints are related to the regulation of affect states. The COVID-19 pandemic has caused a prolonged period of perturbations to the daily lives of people across the globe, providing an unparalleled opportunity to investigate how fluctuations in positive and negative affect relate to the evolution of mood complaints.Methods. 228 participants from the Boston College … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Network simulations predict this exact result; as network connectivity increases, symptoms become more variable (15). Recent empirical evidence for this claim found that emotion network connectivity was positively related to the absolute, but not signed, change in depression severity (16).…”
Section: Introductionmentioning
confidence: 91%
“…Network simulations predict this exact result; as network connectivity increases, symptoms become more variable (15). Recent empirical evidence for this claim found that emotion network connectivity was positively related to the absolute, but not signed, change in depression severity (16).…”
Section: Introductionmentioning
confidence: 91%
“…In the case of symptoms that make up a depression sum score, higher covariance between symptoms necessarily increases the variability of a total score ( 16 ). Recent empirical evidence for this claim found that emotion network connectivity was positively related to the absolute, but not signed, change in depression severity ( 17 ).…”
mentioning
confidence: 99%